Complicaciones infecciosas puerperales en mujeres del Hospital Téofilo Dávila. - Apolo Echeverría, Yanice Gianella (2016)
Despite advances of the science into obstetric practice and the employment of modern and powerful antibiotics, puerperal infection continues to be one of the leading causes of morbidity in obstetrical patients. Type of study: descriptive, retrospective. Objectives: 1. To identify the infectious complications in the mediate puerperium postpartum and postcesarean; 2. To know infectious complications advanced puerperium postpartum and postcesarean; 3. To indicate the frequency of the puerperal infectious complications in the postpartum and postcesarean. Emplacement and / or place of study: Teofilo Davila Hospital from the town of Machala. Participants: 2400 from patients’ medical records puerperal women during the year 2015. Sample: 60 patients that complied with the criteria for inclusion being found in state of an infectious pathological puerperium whose childbirth was vaginal or by Caesarean section. Materials and methods: Application of "Form of collection of data" to the medical records of patients in the study. Results: The following infectious complications were obtained: 58% puerperal mastitis, 33% abdominal surgical wound infection, 8% of puerperal endometritis. Conclusions: puerperal infection that predominates in the mediate puerperium postpartum and postcesarean is the mastitis with breast engorgement; the puerperal infection that prevails in the late puerperium postpartum is the mastitis with predominance of an infectious mastitis and in the advanced puerperium postcesarean preponderates the infection of the surgical abdominal wound accompanied by dehiscence. The frequency of puerperal infection in the vaginal postpartum is 47% and the postcesarean is of 53%. Keywords: infectious complications, puerperium, mastitis, endometritis.